Konsep Parenting Era Society 5.0 (Analisis Surah Al-Ahzab Ayat 21 Tafsir Al-Mishbah) - S. Madani, Muallifah (Advances in Humanities and Contemporary Studies, 2024)
Advances in technology today, make everyone's lifestyle change. One of them is the education sector, the main education that will be given by parents to children. This will be the focus point of this research.The ease of accessing information today is quite troubling because children can easily consume various information in the form of various dimensions (audio, visual and audio-visual). So it is very possible that they will receive hoax information and so on. Namely information that contains negative content. Not only that, children also have a tendency to be so engrossed in playing with their gadgets that they forget the life around them.This is neither unavoidable for parents nor is it the best way to isolate them from this digital advancement. However, parents should better understand and follow the times. Because the wrong educational process will experience deviations so that it slips into something that is not expected.In this era of society 5.0, a technological transformation allows access in virtual spaces that feel like physical spaces. In the era of society 5.0, it is possible for children who study formally directly to deal with robots or applications specifically designed to replace educators or controlled by educators remotely and this is interactive. Therefore, a new concept is needed so that parental education for children remains adaptive, namely smart modeling and techno modeling.